Service quality and technology for performing Hajj - Hussin, Siti Rahayu; Abd Rahman, Azmawani; Abdul Latiff, Ahmed Razman (Universiti Putra Malaysia Press, 2014)
This case highlights the success of Lembaga Tabung Haji as the sole provider of Hajj (pilgrimage) management services for Muslims residing in Malaysia to perform Hajj in the Holy Land. A very significant contributing factor to the success of Lembaga Tabung Haji was the services provided by various staff under Tabung Haji as well as related parties. This case specifically discuss about the opportunities and challenges for the Guidance Division, a division under the Hajj Department, focusing on two types of Tabung Haji staff: PIHTAS (Hajj facilitators in the Holy Land) and PEKTA (Hajj course facilitators). The case highlighted the need for guidance among the prospective pilgrims both while in Malaysia and in the Holy Land. The knowledge on hukum and the support (such as counselling) given by PEHTAS & PEKTA helped ease the challenges faced by prospective pilgrims who were in unfamiliar places performing unfamiliar rituals. Delivery of service and service quality directly influenced the satisfaction of these pilgrims. In the future, the introduction of technology to assist delivery of the services might further improve service quality, hence increasing customer satisfaction with Lembaga Tabung Haji as a whole.